PERAN PENYALURAN DANA CORPORATE SOSIAL RESPONSIBILITY (CSR) DALAM MENINGKATKAN KEPERCAYAAN NASABAH - Nawawi, M. Kholil; Astarini, Fera (Al-Infaq: Jurnal Ekonomi Islam, 2010)
Corporate social responsibility (CSR), also known as Corporatel responsibility, corporate citizenship, responsible business, sustainable responsible business (SRB), or corporate social performance, is a form of corporate self-regulation integrated into a business model. Essentially, CSR is the deliberate inclusion of public interest into corporate decision-making, and the honoring of a triple bottom line: People, Planet, Profit. So the core of CSR is how form a company that has a sense of responsibility towards the welfare of society (people) and the preservation of the environment (planet) around them to keep not forget to takeaprofit (profit) long-term will be obtained. However, it essentially is titled to aid to an organization’s mission as well as a guide to what the company stands for and willuphold to its stakeholders. The business world act to encourage a healthy economic growth taking into account environmental factors. Now the business world is no longer only concerned with the company’s financial records only (single bottom line), but already includes the financial aspects, social aspects, and environmental aspects of the so-called triple bottom line. This is the key concept of sustainable development.